KONSEP DIRI KOMUNITAS MUSLIMAH MOTIVATION (MUMO) DIKOTA PEKANBARU - Yanti, Fitri; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at the Secretariat of the Motivation Muslimah Community at the Great Mosque of An-nur. The purpose of this study was to determine the Self-Concept of the Motivation Muslim Community in Pekanbaru City. The topic of focus in this research is to know the self-concept of the Muslimah community in Peknabaru. There are 4 informants in this study. The author uses qualitative methods and uses purposive sampling technique. The data instruments. were interviews and documentation. From the research conducted, the authors found that what led to the Self-Concept of the Muslimah Motivation Community in Pekanbaru City was because they wanted to join the community because it arose from their own desires. Before they want to enter the community they find out what self-concept as a Muslim woman and what an Ideal Muslim woman is like, they have already sought out and thought about it because of their previous reflections and thoughts. Keywords: Self-Concept, Community, Muslimah Motivation Pekanbaru